Technology-Based Factors of University Students' Intentions to Use Ai-Enabled Mobile Banking: The Moderating Role of Personal Innovativeness - Nurul Hidayah; Latifah Dian Iriani (IECON: International Economics and Business Conference, 2024)
This study examines the technology based factors affecting university students' intents to embrace AI-enabled mobile banking in Sorong City, Southwest Papua, Indonesia. Employing a quantitative methodology, data were gathered from 159 students via surveys and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The findings reveal that positive attitudes towards AI and perceived trust significantly effect the intention to use AI-enabled mobile banking. However, contrary to existing literature, relative advantage and security did not demonstrate significant relationships with intention to use Ai enabled- mobile banking. Personal innovativeness as moderating factor does not moderate the relationship between latent variables and the intention to use AI-enabled mobile banking. These findings suggest that students’ perceptions of AI technologies differ from those in other contexts, underscoring the importance of tailored strategies by financial institutions. Despite AI's growing importance in mobile banking, limited research addresses its adoption determinants and the moderating role of personal innovativeness in underdeveloped regions like Sorong City. The study also adds to the body of knowledge on technology adoption in developing regions, which can inform mobile banking and AI integration research and practice.